¬Relationship of ACTN3-Promoter gene polymorphism and Alpha actin-3 concentration with performance of Original Arabian-WAHO horses - Turki, Waleed Zaben; Al-Anbari, Nasr Noori (Journal of Kerbala for Agricultural Sciences, 2023)
The research was conducted in the Iraqi Equestrian Club (15 km west of Baghdad city center) for the period from 10/1/2021 to 11/30/2022, with the aim of detecting polymorphism in the ACTN3 gene (promoter region) in original Arabian horses (WAHO). There were two variants (2 SNPs) in the Promoter region, which are rs1150531051 with polymorphism of TT, TC and CC, and the frequency of the two alleles T and C amounted to 0.34 and 0.66), and the variant rs1144978872 with polymorphism of GG, GA and AA, and the frequency of the two alleles G and A amounted to 0.68 and 0.32. It was observed that there is a positive and significant regression of the depth of respiration after the exercises on the concentration of alpha-actin 3, and the regression of the number of respiration times after the exercises on alpha-actin-3 and the ratio of alpha-actin-3 to the RNA level is positive and significant and reached 0.905 and 0.569, and there is a positive and significant regression (P≤0.05) for the speed of horses on the concentration of α-actin 3 (0.552 m/min) as well as on the ratio of α-actin 3 to RNA level (0.617 m/min) in purebred Arabian horses. We can conclude, through studying the genetic features in the ACTN3 gene, the promoter region, that it can be adopted in setting strategies for genetic improvement in horses. The rates of velocity and the number of body dimensions increased with the increase in the concentration of actin, and some values of the coefficient of determination (R2) were moderate